Strategi Pengembangan Sektor Pariwisata Dinas Kebudayaan dan Pariwisata Kabupaten Kepulauan Talaud - Takaliuang, Arfan; Ogotan, Martha; Plangiten, Novva (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: This study is to determine the strategy of development of tourism sector of Culture and TourismDistrict Talaud islands. Department of Culture and Tourism Talaud district has an important role indeveloping the tourism sector and is responsible for the management and maintenance of tourism potentialas well as the facilities and infrastructure that exist. One example of the ineffectiveness of the strategyDepartment of Culture and Tourism in developing the tourism sector is, there are many sights that havenot been managed properly, also the absence Determination levy entry fee for each visitor who comes inlocation, as well as limitations and lack of facilities supporting tourism becomes one of the factors thathinder tourism management. Lack of promotion and lack of awareness and community participation in thetourism sector to make tourism in Talaud Regency difficult to develop. This study uses Qualitative ResearchMethods SWOT analysis techniques through interviews with 10 Informants, observation and documenttracking instrument assisted an additional form of interview guidelines using data analysis techniques ofdata reduction, data presentation, and of the conclusion. Based on the research results through a SWOTanalysis. The following are the results of the analysis: Department of Culture and Tourism Talaud districthas the strength of the tourism sector will be an asset that is more wealth of art and culture and tourismasset, weaknesses in the Department of Culture and Tourism is not optimal promotion and tourismmarketing, the opportunities that exist in the Department of Culture and Tourism in developing the tourismsector in the District Talaud is stakeholder support tourism and culture, especially the Provincial andNational strong in the Development of Culture and Tourism areas, where as the challenges faced by theDepartment of Culture and Tourism in developing the tourism sector is the level of competition among theregions in which travel product offerings on the above conclusions, are suggested to be cooperationbetween, the Department of Culture and Tourism with the private sector or investors, then the OfficeCulture and Tourism and the local government must facilitate all the needs of tourism, especially in termsof facilities and infrastructure and training-training and promotion.Key Words: the role of the Agency in the implementation of regional staffing mutations.